Implementasi Yuridis Undang-Undang Nomor 13 Tahun 2011 Tentang Penanganan Fakir Miskin dalam Peraturan Daerah di Kota Yogyakarta - bagus anwar hidayatulloh (Universitas Islam Darul Ulum, 2021)
Abstract Specifically regulate the poor are expected to provide comprehensive arrangements in an effort to improve the welfare of the poor in a more planned, directed and sustainable manner. However, in the implementation of this law, to this day it has not been able to solve poverty cases completely and evenly. Previously, the legal basis for efforts to improve the welfare of the poor was still partial and spread across various provisions of laws and regulations. Then the government enacted Undang – undang Nomor 13 Tahun 2011 tentang Penanganan Fakir Miskin. With the existence of a law that specifically regulates the poor, it is expected to provide comprehensive regulations in an effort to improve the welfare of the poor in a more planned, directed and sustainable manner, especially in the city of Yogyakarta in the form of a Regional Regulation. This research aims to determine the juridical implementation of Undang – undang Nomor 13 Tahun 2011 tentang Penanganan Fakir Miskin di Yogyakarta. The type of research used in this research is normative juridical research so that the approach is more towards the approach of regional regulations and other regulations made by the Yogyakarta City Government. The results of this study indicate that when viewed from the characteristics of the problem, the Yogyakarta City Government in implementing Undang-Undang Nomor 13 Tahun 2011 tentang Penanganan Fakir Miskin materially has implemented the mandate of the Law. However, the researcher found that there were formal defects in the application of the laws and regulations, namely that the Yogyakarta City Government had not implemented Undang-Undang Nomor 13 Tahun 2011 tentang Penanganan Fakir Miskin the Management of the Poor as a legal basis for implementation. However, materially, the Yogyakarta City Government has implemented related policies regarding the handling of the poor in Yogyakarta City. Keywords : The Poor, Regulation, Yogyakarta.